1,2-Dihydropyridazines as Versatile Synthetic Intermediates - Britten, Thomas K.; Kemmitt, Paul D.; Halcovitch, Nathan R.; Coote, Susannah C. (Synlett, 2020)
The reactivity of 1,2-dihydropyridazines under various conditions is described, leading to the formation of a variety of products, including 2-aminopyrroles, phenylenediamines, and several novel heterocyclic motifs.
Keywords: dihydropyridazines; heterocycles; pyrroles; diazetidines; phenylenediamines